Supportive caching strategies for MANET: a review - Phani Kumar, NN.; Amuthadevi, C. (International Journal of Engineering and Technology, 2018)
Caching in mobile computing surroundings is a capable approach which could improve information get right of entry to performance and lessen the heavy verbal exchange between client and server. Caching permits sharing and coordination of reserved records between cell hosts. In this paper all the caching schemes for wired, ad hoc and internet mobile advert hoc community are mentioned and compared in terms of cache resolution and cache substitute coverage.